Economic Evaluation of Ticagrelor Plus Aspirin Versus Aspirin Alone for Acute Ischemic Stroke and Transient Ischemic Attack - Chen, Jigang; Ji, Linjin; Tong, Xin; Han, Mingyang; Zhao, Songfeng; Qin, Yongkai; He, Zilong; Jiang, Zhiqun; Liu, Aihua (Frontiers in Pharmacology, 2022)
Background: Although ticagrelor plus aspirin is more effective than aspirin alone in preventing the 30-day risk of a composite of stroke or death in patients with an acute mild-to-moderate ischemic stroke (IS) or transient ischemic attack (TIA), the cost-effectiveness of this combination therapy remains unknown. This study aims to determine the cost-effectiveness of ticagrelor plus aspirin compared with aspirin alone. Methods: A combination of decision tree and Markov model was built to estimate the expected costs and quality-adjusted life-years (QALYs) associated with ticagrelor plus aspirin and aspirin alone in the treatment of patients with an acute mild-to-moderate IS or TIA. Model inputs were extracted from published sources. One-way sensitivity, probabilistic sensitivity, subgroup analyses were performed to test the robustness of the findings. Results: Compared with aspirin alone, ticagrelor plus aspirin gained an additional lifetime QALY of 0.018 at an additional cost of the Chinese Yuan Renminbi (¥) of 269, yielding an incremental cost-effectiveness ratio of ¥15006 (US$2207)/QALY. Probabilistic sensitivity analysis showed that ticagrelor plus aspirin had a probability of 99.99% being highly cost-effective versus aspirin alone at the current willingness-to-pay threshold of ¥72447 (US$10500)/QALY in China. These findings remain robust under one-way sensitivity and subgroup analyses. Conclusions: The results indicated that early treatment with a 30-day ticagrelor plus aspirin for an acute mild-to-moderate IS or TIA is highly cost-effective in China setting.